2007
DOI: 10.1590/s1413-86702007000200023
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial outbreak of Pantoea agglomerans in a pediatric urgent care center

Abstract: Pantoea agglomerans is a Gram-negative bacterium whose isolates can be found in blood cultures and other secretions. This article described one outbreak of sepsis due to this bacterium in the pediatric urgent care center of a tertiary hospital, in Brasilia, Federal District. This was a case-control study and it evaluated the risk factors for acquisition of nosocomial sepsis caused by Pantoea agglomerans. Six case-patients and 15 control-patients have been found. The risk factors were: vomiting in the internmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 11 publications
1
26
0
3
Order By: Relevance
“…Pantoea spp. have been infrequently isolated in Madagascar [3] and can be associated with human disease and nosocomial spread [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Pantoea spp. have been infrequently isolated in Madagascar [3] and can be associated with human disease and nosocomial spread [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Now classified as an opportunistic human pathogen, P. agglomerans was implicated in US and Canadian outbreaks of septicaemia caused by contaminated closures on infusion fluid bottles [26]. P. agglomerans has since been associated in the contamination of intravenous fluid, parenteral nutrition, blood products, propofol, and transference tubes, causing illness and even death [27-31]. P. agglomerans has also been obtained from joint fluids of patients with synovitis, osteomyelitis, and arthritis [17], where infection often occurs following injuries with wood slivers, plant thorns, or wooden splinters [17,32-34].…”
Section: Plant Pathogens That Infect Humansmentioning
confidence: 99%
“…All cases except one succumbed to death. The study by Bicudo et al 9 reported the predilection of this organism for the lungs. In this outbreak, all cases had multiorgan involvement including lung infection.…”
Section: Discussionmentioning
confidence: 97%